Outcome Measurement of Counseling Interventions: A Data-Driven Approach to Assessing the Effectiveness of Therapy Programs - Fauzi Aldina; Lusiana Rahmadani Putri; Deng Jiao (Research Psychologie, Orientation et Conseil, 2024)
Measuring the effectiveness of counseling interventions is essential for ensuring the quality and impact of therapy programs. However, assessing therapeutic outcomes can be challenging due to the subjective nature of mental health improvements and the diversity of therapeutic approaches. A data-driven approach offers an opportunity to quantitatively evaluate the effectiveness of these programs, enabling a more objective assessment of therapy outcomes. This study aims to develop and implement a data-driven model for measuring the outcomes of counseling interventions. The goal is to provide a structured and reliable method to assess the effectiveness of therapy programs across various mental health conditions. A mixed-methods approach was used, incorporating both quantitative and qualitative data. Quantitative data were collected using standardized mental health assessment tools such as the Depression Anxiety Stress Scales (DASS) and the General Health Questionnaire (GHQ) to track changes in clients' mental health over time. Additionally, qualitative data from client feedback and therapist evaluations were analyzed using thematic analysis to capture subjective experiences. Statistical analysis was performed to evaluate the overall effectiveness of the interventions. The data-driven approach demonstrated significant improvements in mental health outcomes across various counseling interventions. Clients reported reductions in symptoms of depression, anxiety, and stress, with quantitative scores showing consistent improvements. Qualitative feedback further supported these findings, with clients highlighting increased emotional resilience and coping strategies as key benefits of the therapy programs. A data-driven approach to measuring counseling outcomes provides a reliable and comprehensive way to assess the effectiveness of therapy interventions. This model can be used to improve the quality of mental health services and guide the development of more effective therapeutic strategies.